Extreme wave value analysis under uncertainty of climate change scenarios off Iberian Peninsula coast - Vieira, Bárbara F. V. (2021)
Extreme wave value analysis under uncertainty scenarios was developed to estimate wave climate characteristics at 17 stations in southwestern European coast off the Iberian Peninsula. A comprehensive wave dataset downscaled with the Wave Watch III (WWIII) model by Meteogalicia under MarRisk Project was used considering results of models from the Coupled Model Intercomparison Project 5 (CMIP5). Descriptive statistics for significant wave height (Hs), peak wave period (Tp), and mean and peak wave direction were performed for historical data (1960−2005), and for projected data in two twenty-year time periods under two Representative Concentration Pathway (RCP) scenarios (2026−2045 and 2081−2100). Hs and Tp extreme values for the study area were obtained using the Gumbel, Fréchet and Weibull probability distributions for the 10-, 50-, and 100-year return period. Obtained results showed that: historical Hs values decrease from North to South and are higher than those calculated in any of the RCPs future scenarios; mean Tp values appear to be constant in all stations; and means for peak and mean direction have higher frequency of occurrence in Q4 (270°−360°). This study also allowed the computation of Hs and Tp values for 100-year return period, which can be used as design criteria for structural analyses in maritime works